Awareness and Usage of Internet Banking Facilities in Pokhara Metropolitan, Nepal - Ranabhat, Deepesh; Poudel, Hemkanta; Ranabhat, Mala (Journal of Business and Management, 2022)
Background: Many businesses’ operating models have shifted as a result of evolution of the internet, and the banking industry has been no exception in recent years.Objectives: The purpose of this study is to determine the internet banking awareness and usage in Pokhara Metropolitan, Nepal. Further, it investigates the factors that affect the internet banking usage in the research area.Methods: A quantitative approach has been employed in this study using descriptive and analytical research design. This study is based on a survey of 225 customers of commercial banks living in Pokhara which are selected purposively.Results: This study finds that the majority of the respondents are aware and use the internet banking services provided by banks mostly for checking the account and bank statement, topping up the mobile phone, transferring money between accounts, and paying utility bills. Similarly, it finds that time-savings, 24 hours’ availability, easy banking transactions, speediness, and reliability are the primary reasons for internet banking usage. Whereas, insufficient understanding of internet banking, preference of traditional banking over internet banking, lack of internet using habit are the major reasons for no use of internet banking services. The regression analysis shows that the factors such as awareness, access, security, and bank support have a significant positive effect on internet banking usages.Conclusion: Internet banking is widely used in Pokhara Metropolitan. Further, increase in awareness level, internet access, secure internet banking, and bank’s support helps to increase the internet banking usage in Nepal.